A randomized phase 2 study comparing EC or CMF versus nab-paclitaxel plus capecitabine as adjuvant chemotherapy for nonfrail elderly patients with moderate to high-risk early breast cancer (ICE II-GBG 52) - Minckwitz, Gunter von; Conrad, Bettina; Reimer, Toralf; Decker, Thomas; Eidtmann, Holger; Eiermann, Wolfgang; Hackmann, John; Möbus, Volker; Marmé, Frederik; Potenberg, Jochem; Stickeler, Elmar; Simon, Eike; et al. (Cancer, 2015)
BACKGROUND Although greater than 40% of breast cancers occur in patients aged ≥65 years, these individuals are frequently undertreated. Taxane-based adjuvant chemotherapy is considered the treatment of choice but to the authors' knowledge has only limited evidence in elderly patients. METHODS Patients aged ≥65 years with a Charlson comorbidity index ≤2 and pT1/2 pN0/1 disease and either human epidermal growth factor receptor 2 (HER2)-positive, hormone receptor-negative, grade 3 (according to Common Terminology Criteria for Adverse Events [version 3.0]), high uPA/PAI-1 or any stage pT3/4 pN2/3 breast cancer were randomized to receive 4 cycles of adjuvant epirubicin and cyclophosphamide (EC) (epirubicin at a dose of 90 mg/m2 and cyclophosphamide at a dose of 600 mg/m2 intravenously [iv] on day 1 every 3 22 days) or 6 cycles of cyclophosphamide, methotrexate, and 5-fluorouracil (CMF) (cyclophosphamide at a dose of 500 mg/m2, methotrexate at a dose of 40 mg/m2, and 5-fluorouracil at a dose of 600 mg/m2 iv on days 1 plus 8 every 29 days) versus 6 cycles of nab-paclitaxel and capecitabine (nPX) (nab-paclitaxel at a dose of 100 mg/m2 iv on days 1, 8, and 15 every 21 days with 1 week of rest every 6 weeks plus capecitabine at a dose of 2000 mg/m2 orally on days 1-14 every 21 days). Primary endpoints were treatment discontinuations and overall frequency of adverse events. RESULTS Thirteen of 198 patients (6.6%) discontinued EC/CMF and 69 of 193 patients (35.8%) discontinued nPX (P<.001) with 1 and 5 deaths observed during treatment, respectively. Grade 3 to 5 adverse events were more frequent among patients treated with EC/CMF (90.9%) than among those treated with nPX (64.8%) (P<.001), with hematological toxicities being more frequent with EC/CMF (88.4% vs 22.3%; P<.001), but nonhematological toxicities (hand-foot syndrome, diarrhea, mucositis, fatigue, sensory neuropathy, thromboembolisms, and metabolic disorders) being more frequent with nPX (58.5% vs 18.7%; P<.001). None of the geriatric scores (Charlson comorbidity index, Vulnerable Elders Survey [VES-13], Instrumental Activities of Daily Living [IADL], and G8) independently predicted grade 3 to 5 toxic events or treatment discontinuations. No differences in survival between the treatment groups were observed after 22.8 months. CONCLUSIONS Compared with EC/CMF, treatment with nPX led to more treatment discontinuations and nonhematological toxicities in elderly patients with moderate or high-risk breast cancer. Cancer 2015;121:3639-3648. © 2015 American Cancer Society.
Gesehen am 25.06.2020